Biochemical Basis and Therapeutic Implications of Angiogenesis - Mehta, Jawahar L.; Mathur, Pankaj; Dhalla, Naranjan S. (Advances in biochemistry in health and disease ;, 2017)
This book covers the latest developments in the therapeutic implications of angiogenesis, ranging from angiogenesis in the brain, angiogenesis in cancer, angiogenesis' role in atherosclerosis and heart disease as well as metabolic disorders and peripheral vascular disease. The book is comprehensive in its coverage of angiogenesis in a diverse set of diseases and examines the role of cellular and subcellular structures during the development of angiogenesis. Well-organized and thorough, this is an ideal book for researchers and biomedical engineers working in the field of therapeutic implications of angiogenesis. This book also: Covers the basics of the physiology of angiogenesis, including VEGF pathways in angiogenesis, integrins in angiogenesis, angiogenesis and exercise physiology, and more Details the role of angiogenesis in atherosclerosis and heart disease, including vascular endothelial growth factor and atherosclerotic plaque progression as well as angiogenesis and heart failure Illustrates in detail brain angiogenesis after stroke and the relationship between angiogenesis and Alzheimer's disease.